IMPACT OF YOGIC PRACTICES AND NEUROMOTOR TRAINING ON REACTION TIME AND HAND–EYE COORDINATION AMONG FEMALE STUDENTS - Mr. A. THOOYA ALEX; Dr. C. DURAI (The Bioscan, 2025)
Hand–eye coordination and reaction time are vital for both health and academic achievement in female undergraduate education college students, as they significantly influence motor learning and participation in physical activities (Schmidt & Lee, 2014). This study set out to assess how yogic practices and Neuromotor training affect these two key abilities in female undergraduate education students. A total of 48 female undergraduate students (aged 22–26 years) from education college were randomly assigned into three groups (n = 16 each): the Yogic Practice Group (YPG), the Neuromotor Training Group (NMTG), and the Control Group (CG). The YPG and NMTG participants underwent six weeks of their respective training interventions, while the CG received no structured intervention. Reaction time was assessed using the Ruler Drop Test, and hand–eye coordination was measured with the Alternate Hand Wall Toss Test. Data were analysed using ANCOVA, with pre-test scores as covariates. Results revealed that both the YPG and NMTG demonstrated significant improvements after six weeks; however, the NMTG exhibited significantly greater gains in both reaction time and hand–eye coordination compared to the YPG and CG. These findings suggest that neuromotor training is more effective than yogic practices for enhancing psychomotor performance in female undergraduate students of education.